2016
DOI: 10.1136/annrheumdis-2016-eular.2625
|View full text |Cite
|
Sign up to set email alerts
|

SAT0408 Anti Tnf-α Therapy Provides Beneficial Effects on Choroidal Thickness Increase in Patients with Active Ankylosing Spondylitis: A Possible Mechanism of Infliximab Effectiveness in Suppressing Uveitis Attacks

Abstract: BackgroundPatients with ankylosing spondylitis (AS) have higher choroidal thickness values (CT) compared to controls.ObjectivesTo quantitatively asses the profile of CT in patients with AS using optical coherence tomography (OCT), and to examine whether the posterior eye segment abnormalities in active AS patients were reversible by infliximab therapyMethodsThirty-one patients with AS receiving infliximab therapy and 24 healthy controls were enrolled. Patient's clinical and demographic characteristics were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Karkucak et al compared CT in 31 patients with active AS and in 24 healthy subjects. Choroidal thickness was thicker in the patient group, although the difference was not statistically significant 22 . As the study did not include a sample size calculation, it may have been underpowered due to the difference between group sample sizes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Karkucak et al compared CT in 31 patients with active AS and in 24 healthy subjects. Choroidal thickness was thicker in the patient group, although the difference was not statistically significant 22 . As the study did not include a sample size calculation, it may have been underpowered due to the difference between group sample sizes.…”
Section: Discussionmentioning
confidence: 84%
“…Choroidal thickness was thicker in the patient group, although the difference was not statistically significant. 22 As the study did not include a sample size calculation, it may have been underpowered due to the difference between group sample sizes. Conversely, the present study compared biological treatment-naive patients with healthy subjects who were matched by factors known to affect CT. 13 Under these conditions, our results provide robust confirmation that the choroid is thicker among patients with AS than in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Mean CT was significantly decreased after 6 months (CTat baseline was 347.5 ± 114.4 μm, CTafter 6 months was 326.5 ± 99.7 μm; p = 0.018). 25 Kola et al 2 found no correlation between CT and BASDAI or disease duration in AS patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports support our findings. Karkucak et al 25 evaluated CT in 31 patients with active AS at baseline and after 6 months of infliximab treatment. Mean CT was significantly decreased after 6 months (CT at baseline was 347.5 ± 114.4 μm, CT after 6 months was 326.5 ± 99.7 μm; p = 0.018) 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation